The Influence Of Complaint Handling And Quality Of Public Services Of "Broadcasting" Applications On South Tangerang Smart City Program - Imam Chairudin; Muh. Kadarisman Kadarisman (INFOKUM, 2022)
This study aims to determine the effect of complaint handling and the quality of public service of the "Broadcast" application on the South Tangerang Smart City program. This research method uses a quantitative approach by distributing questionnaires to respondents and then processing the results of the data with the help of the SPSS application. This research has the result that there is a partial influence between the handling of complaints against Smart City with a t count of 2.291 > t table of 2.179 or 0.024 <0.05, there is a partial influence between the quality of service to Smart City with a t count of 7.285 > t table of 2.179 or 0.000 <0.05, there is a simultaneous effect on complaint handling and service quality on Smart City with an F count of 59.641 > F table 3.806 and a significance of 0.000 <0.05.